Challenges in Microsurgical Reconstruction for Craniofacial Osteomyelitis With Resultant Osteonecrosis. Issue 7 (October 2019) - Couto, Rafael A.; Sinclair, Nicholas R.; Lamaris, Gregory; Durand, Paul; Knackstedt, Rebecca; Aliotta, Rachel; Gastman, Brian R.
Abstract : Introduction: Chronic osteomyelitis is characterized by compromised blood supply and eventual osteonecrosis. Definitive treatment requires aggressive resection of affected bone. The resultant defect poses a unique challenge to reconstructive surgeons. Much of the literature on craniofacial osteomyelitis focuses on infection eradication, rather than subsequent reconstruction. This article reports representative cases from our experience with free flap reconstruction for defects secondary to chronic osteomyelitis of the craniofacial skeleton. Methods/Results: The authors selected 5 of the most difficult reconstructive cases of craniofacial osteomyelitis from our experience in a single tertiary referral institution with a follow-up of at least 6 months. Three of the 5 cases arose in the setting of previous head and neck cancer treated with resection and radiation therapy. One case had a previous surgical craniotomy complicated by osteomyelitis and multiple failed alloplastic reconstructions. The final case was due to multiple gunshots to the head, with subsequent cerebral and cranial abscess (>1000cc). In each case, the defect was successfully treated with free tissue transfer. Two cases required creation of recipient vessels with an arteriovenous loop. Conclusions: Free tissue transfer provides a versatile and effective tool in the reconstruction of extensive craniofacial osteomyelitis defects. Furthermore, the addition of vascularized tissue can protect against further episodes of osteomyelitis. Finally, arteriovenous loops can be employed successfully when prior radiation and infection of the wound bed precludes the use of local recipient target vessels.